1999
DOI: 10.1053/bbmt.1999.v5.pm10371361
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of tacrolimus whole blood levels to efficacy and safety outcomes after unrelated donor marrow transplantation

Abstract: Tacrolimus has proved effective for preventing acute graft-vs.-host disease (GVHD) after unrelated donor marrow transplantation, but the therapeutic window is apparently narrow. Therapeutic drug monitoring could potentially be used to guide dose modifications, but the optimal target range of tacrolimus blood concentrations is unknown. We determined whether acute GVHD and renal dysfunction correlated with tacrolimus whole blood levels as measured by the IMx assay. Data were analyzed for 97 adults treated in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 7 publications
5
54
1
2
Order By: Relevance
“…tacrolimus therapy at the daily dose of 0.022 mg/kg on day À1 by continuous infusion for more than 24 h. This represents a 30% dose reduction compared with the recommended starting dose of 0.03 mg/kg, 13 and is consistent with current product guidelines for reduction of tacrolimus dose when administered concomitantly with voriconazole. 12 Tacrolimus blood concentrations were serially monitored while patients were receiving i.v.…”
Section: Methodssupporting
confidence: 72%
“…tacrolimus therapy at the daily dose of 0.022 mg/kg on day À1 by continuous infusion for more than 24 h. This represents a 30% dose reduction compared with the recommended starting dose of 0.03 mg/kg, 13 and is consistent with current product guidelines for reduction of tacrolimus dose when administered concomitantly with voriconazole. 12 Tacrolimus blood concentrations were serially monitored while patients were receiving i.v.…”
Section: Methodssupporting
confidence: 72%
“…The upper range of 20 ng/ml was derived from analyses of correlated toxicities. 1,5 In contrast, the relationship between blood concentration of tacrolimus and control of acute GVHD using lower target levels has not been well defined. Przepiorka et al 2 reported that tacrolimus levels of o5 ng/ ml were associated with an increased risk of acute GVHD after unrelated donor marrow transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Przepiorka et al 17 reported a lack of correlation between the levels of tacrolimus and risk of acute GVHD within a concentration range of 5-40 ng/ml, but a significant increase in the risk of nephrotoxicity above levels Ͼ20 ng/ml. It is noticeable that the blood level of tacrolimus in this patient, measured the day before the start of pancreatitis, was within the target range of 10-20 ng/ml.…”
Section: Discussionmentioning
confidence: 99%